2014
DOI: 10.1016/j.bbadis.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β(1-42) protofibrils stimulate a quantum of secreted IL-1β despite significant intracellular IL-1β accumulation in microglia

Abstract: Neuroinflammation is a characteristic feature of the Alzheimer’s disease (AD) brain. Significant inflammatory markers such as activated microglia and cytokines can be found surrounding the extracellular senile plaques predominantly composed of amyloid-β protein (Aβ). Several innate immune pathways, including Toll-like receptors (TLRs) and the NLRP3 inflammasome, have been implicated in AD inflammation. Aβ plays a primary role in activating these pathways which likely contributes to the progressive neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
(71 reference statements)
2
33
0
Order By: Relevance
“…Primary microglia were isolated from both wild-type (WT) and CD47 −/− mice and the cytokine response to Aβ(1-42) protofibrils was assessed. We have previously investigated the time course for protofibril-induced TNFα secretion in primary microglia and found that 6 h is an appropriate time frame for time-dependent studies [37]. The protofibril response in the current study was consistent with our previous work in WT microglia showing little TNFα secretion at 2 h but a significant increase after 6 h of microglia exposure to Aβ(1-42) protofibrils (Figure 4A).…”
Section: Resultssupporting
confidence: 89%
“…Primary microglia were isolated from both wild-type (WT) and CD47 −/− mice and the cytokine response to Aβ(1-42) protofibrils was assessed. We have previously investigated the time course for protofibril-induced TNFα secretion in primary microglia and found that 6 h is an appropriate time frame for time-dependent studies [37]. The protofibril response in the current study was consistent with our previous work in WT microglia showing little TNFα secretion at 2 h but a significant increase after 6 h of microglia exposure to Aβ(1-42) protofibrils (Figure 4A).…”
Section: Resultssupporting
confidence: 89%
“…The inflammatory reaction is a core pathological mechanism of AD [83][84][85]. Inflammatory responses, which are present in obesity and T2DM, are closely related to the development of IR in both peripheral and central tissues, thus may increase the risk of AD [86].…”
Section: Insulin Resistance Affects Brain Inflammatory Reactionmentioning
confidence: 99%
“…Notably, increased IL-1β expression is observed in activated microglia surrounding Aβ plaques in patients with AD and in mouse models of AD. Furthermore, Aβ has been consistently shown to trigger IL-1β secretion in vitro and in vivo [1,24]. Importantly, the activation of the NLRP3 inflammasome is a critical upstream regulator of caspase-1 activation, which results in the maturation and secretion of IL-1β [31].…”
Section: Mitochondrial Ros Promote Nlrp3 Inflammasome Activation and mentioning
confidence: 99%
“…Primary microglia cultures were isolated from postnatal day 1 C57BL/6J mice and cultured as previously described [24]. The brains were removed, and cortices were freed from meninges and blood vessels.…”
Section: Primary Microglia Culturesmentioning
confidence: 99%